Electronic Effects in 1, 3-diaryl-1, 3-diketone Reduction Potentials Correlate with σ0. (4th November 2015) - Gipson, Stephen L.; Garner, Charles M.; Panthi, Basu D.
Abstract : The electrochemical reduction of aryl-substituted dibenzoylmethanes was studied in acetonitrile. They display one-electron couples that are chemically and electrochemically reversible at low concentrations. The formal potentials correlate with only one (σ 0 ) of the various Hammett parameters.